2006
DOI: 10.2337/db05-0624
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y Deficiency Attenuates Responses to Fasting and High-Fat Diet in Obesity-Prone Mice

Abstract: Neuropeptide Y (NPY) stimulates feeding and weight gain, but deletion of the NPY gene does not affect food intake and body weight in mice bred on a mixed genetic background. We reasoned that the orexigenic action of NPY would be evident in C57Bl/6J mice susceptible to obesity. NPY deficiency has no significant effect in mice fed a normal rodent diet. However, energy expenditure is elevated during fasting, and hyperphagia and weight gain are blunted during refeeding. Expression of agouti-related peptide (AGRP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 39 publications
2
56
1
Order By: Relevance
“…Experimental procedures were in accordance to institutional guidelines and regulations. Male C57BL/6J wild-type and npyϪ/Ϫ mice (Patel et al, 2006;Qi et al, 2006), were housed n ϭ 5 per cage in 12 h light/dark cycle (lights on 7:00 A.M.) and ambient temperature 22°C. Chow and water were provided ad libitum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental procedures were in accordance to institutional guidelines and regulations. Male C57BL/6J wild-type and npyϪ/Ϫ mice (Patel et al, 2006;Qi et al, 2006), were housed n ϭ 5 per cage in 12 h light/dark cycle (lights on 7:00 A.M.) and ambient temperature 22°C. Chow and water were provided ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study has shown that infusion of NPY intracerebroventricularly impairs insulin sensitivity and increases endogenous glucose production (Marks and Waite, 1997;van den Hoek et al, 2004). We administered resistin intracerebroventricularly in NPY deficient C57BL/6J mice (npyϪ/Ϫ) (Patel et al, 2006) and performed a hyperinsulinemic-euglycemic clamp and tracer kinetics. Resistin treatment did not change basal or clamp chemistries (Table 3).…”
Section: Npy Mediates the Effect Of Central Resistin On Hepatic Insulmentioning
confidence: 99%
“…Administration of NPY to the paraventricular nucleus (PVH) increases the activity of PVH neurons by presynaptically inhibiting local γ-amino butyric acid release (Cowley et al, 1999) and decreases brown adipose tissue thermogenesis (Egawa et al, 1991). NPY knockout mice have increased energy expenditure (increased O 2 consumption), increased uncoupling protein-1 (UCP-1) in brown adipose tissue and increased cold-evoked thermogenesis in white adipose tissue and are less susceptible to diet-induced obesity (Patel et al, 2006;Chao et al, 2011). In the present study, chickens fed the HF diet for 35 days to induce obesity (fat) were compared with chickens fed the LF diet for 35 days (lean).…”
Section: Involvement Of Agrp In the Hf-induced Decrease In Food Intakementioning
confidence: 99%
“…NPY reduces energy expenditure by decreasing adipose tissue thermogenesis (Egawa et al, 1991;Patel et al, 2006;Chao et al, 2011;Zhang et al, 2014). The obesity of ob/ob mice is attenuated when NPY is knocked out (Erickson et al, 1996;Segal-Lieberman et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation